Samband mellan en längre tillväxtsäsong och en ökad smoltstorlek i Vänerområdet - Fransson, Ann-Marie (Fakulteten för samhälls- och livsvetenskaper, 2008)
Abstract The purpose of this study was to see if there is a connection between smolt length from Brattfors salmon cultivation and temperature. Climate changes are expected to give a higher temperature that could result in a longer growing season for the fish. Cultivated smolt is today bigger than it was before, it is also bigger than the wild salmon. The growth season of salmonids depend on the water temperature, salmonids need 6-80C to grow. Water temperature has been surveyd since the late 50´s in Brattfors. The result shows that it’s now considerable more days per year with higher temperature. Data of the fish length growth includes 2-years old smolt of salmon (Salmo salar L.) and trout (Salmo trutta L.), put out in the Vänern area from 1965 – 2002. This study is includes the tribes of Klarälvssalmon, Gullspångssalmon and Gullspångstrout. Length data was related to growth season, i.e. number of days with a temperature above 60C, in the cultivation basins. The result of this study shows for both tribes of salmon that there is not a relationship between fish length and days of growing temperatures because the regression coefficient was too small. The result for the Gullspångstrout shows a small length increase and the regression coefficient were lager than it was for the tribes of salmon. Sammanfattning Syftet med denna studie var att undersöka ifall det fanns ett samband mellan längdtillväxten hos kompensationsodlad smolt från Brattforslaxodling och temperatur. Klimatförändringar förväntas ge högre temperaturer, vilket för fiskens del skulle visa sig i en allt längre tillväxtsäsong. Odlad smolt är i dag större än vad den varit längre tillbaka i tiden och den är även större än sina vilda artfränder. Fiskens tillväxtsäsong styrs till stor del av vattentemperatur. Generellt kan man säga att laxartade fiskar börjar tillväxa över 6-80C. Information om vattentemperaturen har samlats in sedan slutet av 1950-talet i Brattfors. Resultatet visar att det nu är betydligt fler dagar per år med högre temperaturer. Data om ...